Reliability and sensitivity of visual scales versus volumetry for evaluating white matter hyperintensity progression - Gouw, Alida A.; Flier, W. M. van der; Straaten, E. C. W. van; Pantoni, L.; Bastos-Leite, A. J.; Inzitari, D.; Erkinjuntti, T.; Wahlund, L. O.; Ryberg, C.; Schmidt, R.; Fazekas, F.; Scheltens, P.; et al. (Cerebrovascular diseases, 2008)
Background: Investigating associations between the change of white matter hyperintensities (WMH) and clinical symptoms over time is crucial for establishing a causal relationship. However, the most suitable method for measuring WMH progression has not been established yet. We compared the reliability and sensitivity of cross-sectional and longitudinal visual scales with volumetry for measuring WMH progression. Methods: Twenty MRI scan pairs (interval 2 years) were included from the Amsterdam center of the LADIS study. Semi-automated volumetry of WMH was performed twice by one rater. Three cross-sectional scales (Fazekas Scale, Age-Related White Matter Changes Scale, Scheltens Scale) and two progression scales (Rotterdam Progression Scale, Schmidt Progression Scale) were scored by 4 and repeated by 2 raters. Results: Mean WMH volume (24.6 ± 27.9 ml at baseline) increased by 4.6 ± 5.1 ml [median volume change (range) = 2.7 (-0.6 to 15.7) ml]. Measuring volumetric change in WMH was reliable (intraobserver:intraclass coefficient = 0.88). All visual scales showed significant change of WMH over time, although the sensitivity was highest for both of the progression scales. Proportional volumetric change of WMH correlated best with the Rotterdam Progression Scale (Spearman’s r = 0.80, p < 0.001) and the Schmidt Progression Scale (Spearman’s r = 0.64, p < 0.01). Although all scales were reliable for assessment of WMH cross-sectionally, WMH progression assessment using visual scales was less reliable, except for the Rotterdam Progression scale which had moderate to good reliability [weighted Cohen’s ĸ = 0.63 (intraobserver), 0.59 (interobserver)]. Conclusion: To determine change in WMH, dedicated progression scales are more sensitive and/or reliable and correlate better with volumetric volume change than cross-sectional scales.
Gesehen am 24.03.2021
List of participating centers and personnel: Timo Erkinjuntti, MD, PhD, Michael Hennerici, MD, Christian Blahak, MD, Hansjörg Baezner, MD [und weitere]